Regulated Perovskite Crystallization for Efficient Blue Light‐Emitting Diodes via Interfacial Molecular Network - Wang, Lu; Su, Zhen‐Huang; Shen, Yang; Feng, Shi‐Chi; Xie, Feng‐Ming; Zhang, Kai; Meng, Ke‐Fan; Gao, Xingyu; Tang, Jian‐Xin; Li, Yan‐Qing (Advanced functional materials, 2024)
Metal halide perovskite light‐emitting diodes (PeLEDs) are gaining increasing attention as a promising candidate for the new‐generation display technology. Although tremendous progress has been witnessed in this field, the device performance of blue PeLEDs still lags far behind that of the green and red counterparts. In this work, an effective interfacial engineering is employed to boost the radiative recombination of blue perovskite film by introducing a multifunctional tetraethyl orthosilicate (TEOS) network on the grain‐growth substrate. Benefitting from the strong interaction between the TEOS molecule and perovskite nuclei, the perovskite crystallization dynamics are effectively regulated, contributing to significantly improved emitting film with uniformly distributed halogen and concentrated low‐dimensional domain. Additionally, the TEOS network can distinctly passivate the crystal defects at the buried perovskite interface owing to its adequate electron‐donating sites. Consequently, the target blue PeLEDs featuring a stable emission peak at 488 nm exhibit a champion external quantum efficiency of 17.3%, which is among the highest values to date. The results demonstrate the critical role of the surface molecular characteristics of the grain‐growth substrate in regulating the mixed‐halide blue perovskite crystallization. A multifunctional interface engineering by constructing a tetraethyl orthosilicate molecular network onto the grain‐growth substrate is developed to comprehensively regulate the crystallization dynamics and passivate the buried surface defects of mixed‐halide blue perovskite films, leading to spectrally stable and efficient blue light‐emitting diodes with an external quantum efficiency of 17.3%.